UPAYA MENINGKATKAN KEMAMPUAN MENULIS PESERTA DIDIK MELALUI PENDEKATAN PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) PADA SAMPEL KELAS II UPTD SDN CAMPOR 3 KECAMATAN GEGER KABUPATEN BANGKALAN - Anita Agustini; Fauzi Fadliansyah (SEHRAN (Jurnal Pendidikan Sejarah dan Kewarganegaraan), 2023)
The background of this research is due to the low writing ability of Class II students of UPTD SDN Campor 3, Geger Bangkalan District, which is indicated by the mastery of learning writing material which is only 50%. The objectives to be achieved in this study are: Improving the Writing Ability of Class II Semester II UPTD SDN Campor 3 Geger District, Bangkalan Regency Through the Contextual Teaching and Learning (CTL) Approach. This research is a descriptive study using a class action research design (PTK) which is planned to take place in 2 cycles, each cycle consisting of 4 stages, namely: planning, implementing action, observing, and reflecting. The results of learning improvement research in the first cycle showed that there was an increase in students' abilities. The average competency test score was from 60.18 (before cycle) to 69.11 (after cycle 1) and student learning completeness from 40.74% before the cycle to 70.37% in cycle I. Based on the results in cycle I, in Cycle II carried out several variations of treatment to improve students' abilities in learning and increase their competency test scores. After cycle II there was an increase in students' abilities, the average competency test score was from 69.11 (cycle I) to 75.44 (cycle II) and their learning completeness from 69.11% in cycle I to 100% in cycle II. The use of the Contextual Teaching and Learning (CTL) Learning Approach was able to improve the writing skills of class II UPTD SDN Campor 3 Geger District, Bangkalan Regency.